2021
DOI: 10.1038/s41598-021-83077-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct temporal features of genuine and deliberate facial expressions of surprise

Abstract: The physical properties of genuine and deliberate facial expressions remain elusive. This study focuses on observable dynamic differences between genuine and deliberate expressions of surprise based on the temporal structure of facial parts during emotional expression. Facial expressions of surprise were elicited using multiple methods and video recorded: senders were filmed as they experienced genuine surprise in response to a jack-in-the-box (Genuine), other senders were asked to produce deliberate surprise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…To reduce the dimensionality and extract the low-dimensional features, a nonnegative matrix factorization was applied to the time-series data of the AUs [44][45][46]. This approach helps obtain interpretable features in a low-dimensional space [44].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the dimensionality and extract the low-dimensional features, a nonnegative matrix factorization was applied to the time-series data of the AUs [44][45][46]. This approach helps obtain interpretable features in a low-dimensional space [44].…”
Section: Discussionmentioning
confidence: 99%
“…When subjects experienced surprise, the facial movements were described as frowning, eye-widening, and eyebrow raising (Reisenzein et al, 2006 ). Also, in exploring the distinction in dynamics between genuine and deliberate expressions of surprise, it was found that all expressions of surprise consisted mainly of raised eyebrows and eyelid movements (Namba et al, 2021 ). The facial muscles involved in these movements were: corrugator supercilii, orbicularis oculi , and frontalis .…”
Section: The Specificity Of the Relationship Between Facial Muscle And Emotionsmentioning
confidence: 99%
“…Deliberately posed expressions also contain different patterns of motion than expressions that correspond with genuinely felt emotion (Namba et al, 2017(Namba et al, , 2021. Examining specific physical components of various emotion expressions has demonstrated differences in which expression components are present in genuine vs. posed expressions, but also differences in the temporal patterns of movement (Namba et al, 2017(Namba et al, , 2021.…”
Section: Expressions In Motionmentioning
confidence: 99%
“…Deliberately posed expressions also contain different patterns of motion than expressions that correspond with genuinely felt emotion (Namba et al, 2017(Namba et al, , 2021. Examining specific physical components of various emotion expressions has demonstrated differences in which expression components are present in genuine vs. posed expressions, but also differences in the temporal patterns of movement (Namba et al, 2017(Namba et al, , 2021. These differences may also explain why presenting expressions dynamically rather than statically improves participants' ability to detect whether expressions were genuine or posed (Namba et al, 2018;Zloteanu et al, 2018).…”
Section: Expressions In Motionmentioning
confidence: 99%